Filgrastim Induced Severe Leukocytosis in Sepsis-Associated Leukopenia: A Case Repor - Foroud Shahbazi; Hasanali Karimpour (Research Center for Rational Use of Drugs (RCRUD), 2019)
Sepsis-induced leukopenia occurs in critically ill patients and associated with negative clinical outcomes. A sixty years old patients with respiratory failure, decreased level of consciousness and pneumonia transferred to the intensive care unit. During intensive care stay patients developed late ventilator-associated pneumonia and severe neutropenia. Colony stimulating factor (filgrastim) was initiated for patients. Severe leukocytosis (leukocyte counts of 94000/mm3) was seen with no source of new infection was detected. After filgrastim discontinuation serum leukocyte counts returned to the normal limits with no sequel or complication. Although Hyperleukocytosis may increase the risk of thrombosis and pulmonary edema. Most cases of iatrogenic hyperleukocytosis are well tolerated with no complication.